2018
DOI: 10.1371/journal.pone.0203023
|View full text |Cite
|
Sign up to set email alerts
|

The multi‐ethnic global lung initiative 2012 (GLI-2012) norms reflect contemporary adult's Algerian spirometry

Abstract: BackgroundThe validation of the multi-ethnic GLI-2012 spirometric norms has been debated in several countries. However, its applicability in Algeria has not been verified.AimTo ascertain how well the GLI-2012 norms fit contemporary adult Algerian spirometric data.MethodsThis was a cross-sectional study of a convenience sample of 300 healthy non-smoker adults (50% men, age range: 18–85 years) recruited from the Algiers region general population. All participants underwent a clinical examination and a plethysmog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 41 publications
2
20
0
1
Order By: Relevance
“…In these situations, we relied solely on parent self-reporting to determine eligibility; however, this is common practice in similar population studies that have measured lung function. 9,10,20 We acknowledge the challenges in using self-reported data. Questionnaires are frequently impacted by recall bias and poor understanding of the questions may have affected answers particularly where English was not the first language spoken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these situations, we relied solely on parent self-reporting to determine eligibility; however, this is common practice in similar population studies that have measured lung function. 9,10,20 We acknowledge the challenges in using self-reported data. Questionnaires are frequently impacted by recall bias and poor understanding of the questions may have affected answers particularly where English was not the first language spoken.…”
Section: Discussionmentioning
confidence: 99%
“…9 The Global Lung Function Initiative (GLI)-2012 9 recently developed allage, multi-ethnic reference equations. These reference equations span the 3-95 year age range and cover four major ethnic groups, Caucasian, African-American, North-and South-East Asian, as well as providing values for a mixed/other ethnicity group, 9 and have been validated for several population groups [10][11][12][13] including Caucasian Australians. 14 Several studies have found these reference equations to be unsuitable for some Caucasian and non-Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…This present study is part of a project involving four parts. The first, which was recently published [24], aimed at testing the applicability of the global lung initiative (GLI-2012) norms on a sample of healthy adults living in Algiers. The second, recently published [10], aimed to test the applicability of the Eastern Algeria plethysmographic norms [8] on a sample of healthy adults living in Algiers.…”
Section: Population and Methodsmentioning
confidence: 99%
“…The fourth part, will be the establishment, according to recent international recommendations [25], of plethysmographic norms specific to the population of northern Algeria. For the above reasons, a large part of the methodology of this study has already been the object of previous descriptions [10, 24].…”
Section: Population and Methodsmentioning
confidence: 99%
See 1 more Smart Citation